STUDENTS PERCEPTION OF THE ONLINE LEARNING SPEAKING DURING COVID 19 STUDENTS PERCEPTION in MTS TSANAWIAH MORELLA - siti sania yuliani sidig; siti sania yuliani sidig (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
This research aims to know the students’ perception of online learning during covid 19 and to explore the perceptions of the students about the weakness and the advantages of online learning speaking based on the curriculum. This research used descriptive qualitative as the design. In collecting data, the researcher used a interview with 10 students from eight-grade class students at MTS Tsanawiah Morella. The weakness of online learning is a lack of understanding the explanation from the teacher, and the students saw the material from the handphone, and make them doesn’t understand the material. The advantage is the students more focused on the internet than read the book. The result shows that the eighth-grade class students at MTS Tsanawiah Morella, answer the question from the researcher bout their perception of online learning, many students more choose offline learning than online learning. Because they think that learn from offline learning makes their to more understand the material than online learning. Based on the research, the students feel bored with online learning. It can be concluded that from online learning students should improve the skills of the ICT or technology because they need to more practice about the ICT which can help them. And from online learning, the students can manage the time on the process learning of online class. Key Words: Perception, Online Learning, Covid 19.